Interaction of Rationality of Economic Behavior and Ethnic Preferences in the of Latvia (London Journal of Research In Management & Business, 2025)
Sociological research aimed to understand the extent to which the values and norms of the practiced organizational culture adopted at the enterprises/organizations of Latvia are shared by economic actors as rational ways of organizing the economic space, forming solidary relations within the teams of the enterprises, regardless of the ethnic origin and ethnocultural identity of these actors. It was necessary to understand whether there are limitations in the universality of these rational rules, which are somehow connected with the ethno-cultural identity of economic actors. This is important also because the author of the article in his previous sociological study established the fact of the presence of ethnic favoritism in the economic life of Latvia. The sociological research was organized within the framework of the State research program "Vectors of social cohesion: from cohesion around the state-nation (2012-2018) to a cohesive civil community for the security of the state, society and individuals (2024-2025)" (No. VPP-KM-SPASA-2023/1-0002) in 2025, January 6-15. Conducting an online survey on employee cohesion in economic activity in the target group of Latvian employed persons employees and employers. The total sample in the survey n=1008. The sample was formed according to gender, age and place of residence quotas. Most of the organizational culture parameters of Latvians and ethnic minorities that concern them coincide, which indicates a high degree of integration of these population groups into common values ??and norms determined by the economic space in Latvia. However, the content of these organizational cultural features of the Latvian population is related to their attitude towards values ??that are oriented towards achieving goals, which are determined by the very nature of the economic and production tasks of the enterprise and the organization. In situations that actualize their national and ethnic identity values ??in the business and interpersonal communication of employees, ethnic differences arise in the understanding of the existing organizational cultural practices. At the same time, the study revealed that the greatest differences in terms of organizational cultural values ??and norms, existing management practices in organizations and enterprises are related to the level of education of the respondents, gender differences and areas of professional employment.
Keywords: Approximate Nearest Neighbor; Dynamic Indexing; Advertisement Retrieval; Performance Degradation; Graph-based Algorithms; Performance; Security; Effect; Momo Data promoter agent and MTN Ivory Coast.; organizational culture; Rationality; cohesion; team building; socio-economic factors; economic actors; ethnic identity